A Critical Role of the IL-1β-IL-1R Signaling Pathway in Skin Inflammation and Psoriasis Pathogenesis - Cai, Yihua; Xue, Feng; Quan, Chen; Qu, Minye; Liu, Na; Zhang, Yuan; Fleming, Chris; Hu, Xiaoling; Zhang, Huang-Ge; Weichselbaum, Ralph; Fu, Yang-Xin; Tieri, David; et al. (Journal of investigative dermatology, 2019)
The IL-1 signaling pathway has been shown to play a critical role in the pathogenesis of chronic, autoinflammatory skin diseases such as psoriasis. However, the exact cellular and molecular mechanisms have not been fully understood. Here, we show that IL-1β is significantly elevated in psoriatic lesional skin and imiquimod-treated mouse skin. In addition, IL-1R signaling appears to correlate with psoriasis disease progression and treatment response. IL-1 signaling in both dermal γδ T cells and other cells such as keratinocytes is essential to an IMQ-induced skin inflammation. IL-1β induces dermal γδ T cell proliferation and IL-17 production in mice. In addition, IL-1β stimulates keratinocytes to secrete chemokines that preferentially chemoattract peripheral CD27 CCR6 IL-17 capable of producing γδ T cells (γδT17). Further studies showed that endogenous IL-1β secretion is regulated by skin commensals to maintain dermal γδT17 homeostasis in mice. Mouse skin associated with Corynebacterium species, bacteria enriched in human psoriatic lesional skin, has increased IL-1β and dermal γδT17 cell expansion. Thus, the IL-1β-IL-1R signaling pathway may contribute to skin inflammation and psoriasis pathogenesis via the direct regulation of dermal IL-17-producing cells and stimulation of keratinocytes for amplifying inflammatory cascade.